Sandwich Bone Augmentation (SBA) in immediate implant placement post dentoalveolar trauma: a case report - Anton Anton; Poerwati S. Rahajoe; Bambang Dwirahardjo (Journal of Dentomaxillofacial Science, 2017)
Objective: Reporting the application of SBA procedure with titanium mesh as an alternative solution for immediate implant placement in socket with dentoalveolar trauma-induced buccal bone defect.Methods: An 18-year-old female patient visited our department, with a history dentoalveolar trauma and a loss of Â tooth 21. Clinical examination during the implant placement procedure exposed Â a socket with buccal bone defect. SBA with autogenous chin bone graft combined with DFDBA allograft and stabilized with titanium mesh (Ti-Mesh) for buccal defect on which flap reposition was done with tension free primary closure.Results: Ti-Mesh was removed after 3 months which no sign of inflamation appeared, implant was in a stable condition and new bone formation was observed. Subsequently, healing abutment was placed. A one-year observation suggested a good clinical retention with no luxation observed, along with decent functional and esthetic results. CBCT evaluation showed buccal bone thickness preserved.Conclusion: Sandwich bone augmentation with stabilized titanium mesh provides a satisfying result in treating horizontal buccal bone defect.